Immunogenetics and human papillomavirus (HPV) in male genital lichen sclerosus (MGLSc). (December 2020) - Shim, Tang Ngee; Harwood, Catherine A; Marsh, Steven GE; Gotch, Frances M; Quint, Wim; de Koning, Maurits N; Francis, Nick; Jameson, Charles; Freeman, Alex; Minhas, Suks; Dinneen, Michael; Muneer, Asif; et al.
Background The pathogenesis of male genital lichen sclerosus (MGLSc) is controversial. Incriminated factors include infection with human papillomavirus (HPV) and autoimmunity (e.g. Human Leukocyte Antigen [HLA]). To address the roles of HLA and HPV in MGLSc we studied adult Caucasian males with a clinical and histological diagnosis of MGLSc. The men in the study attended two specialised Male Genital Dermatoses Clinics between July 2011 and September 2012 and were selected and phenotyped from the clinical records. DNA was extracted from blood and paraffin-embedded biopsy sections, for HLA and HPV typing, respectively. HLA allele frequencies were compared with those derived from the UK-based Caucasian population. Eighty-eight cases of MGLSc were identified. HPV DNA was detected in 33/88 (37.5%) cases of MGLSc. HPV16 was the most prevalent type found: 11/88 (12.5%) MGLSc. No statistically significant HLA associations were established but HLA-B*35, -B*51, -C*15, -DRB1*04, -DRB1*10 (predisposition) and -DQA1*01 (protection) were revealed as alleles of interest. HPV16-associated MGLSc cases showed no statistically significant association with HLA genotype. The relationship between HPV and MGLSc suggests a passenger effect rather than a pathogenic role. HLA is not associated with MGLSc nor co-existent HPV16.